Chitosan and nematophagous fungi for sustainable management of nematode pests - Lopez-Nuñez, Raquel; Suarez-Fernandez, Marta; Lopez-Moya, Federico; Lopez-Llorca, Luis Vicente (Frontiers in Fungal Biology, 2022)
Plants are exposed to large number of threats caused by herbivores and pathogens which cause important losses on crops. Plant pathogens such as nematodes can cause severe damage and losses in food security crops worldwide. Chemical pesticides were extendedly used for nematode management. However, due to their adverse effects on human health and the environment, they are now facing strong limitations by regulatory organisations such as EFSA (European Food Safety Authority). Therefore, there is an urgent need for alternative and efficient control measures, such as biological control agents or bio-based plant protection compounds. In this scenario, chitosan, a non-toxic polymer obtained from seafood waste mainly, is becoming increasingly important. Chitosan is the N-deacetylated form of chitin. Chitosan is effective in the control of plant pests and diseases. It also induces plants defence mechanisms. Chitosan is also compatible with some biocontrol microorganisms mainly entomopathogenic and nematophagous fungi. Some of them are antagonists of nematode pests of plants and animals. The nematophagous biocontrol fungus Pochonia chlamydosporia has been widely studied for sustainable management of nematodes affecting economically important crops and for its capability to grow with chitosan as only nutrient source. This fungus infects nematode eggs using hyphal tips and appressoria. Pochonia chlamydosporia also colonizes plant roots endophytically, stimulating plant defences by induction of salicylic and jasmonic acid biosynthesis and favours plant growth and development. Therefore, the combined use of chitosan and nematophagous fungi could be a novel strategy for the biological control of nematodes and other root pathogens of food security crops.